PEMBUATAN DAN PEMANFAATAN LIMBAH ORGANIK SEBAGAI PUPUK ORGANIK CAIR DAN PESTISIDA NABATI UNTUK TANAMAN PADI DI KELURAHAN MONTA BARU - Tunnisah, Hijra (Jurnal Wicara, 2023)
Liquid organic fertilizer is one type of fertilizer that is made in a natural way, namely through a fermentation process to produce a solution of the decay results of the materials used. Botanical pesticides are a type of organic pesticide made from organic materials which are efficacious for controlling pests in plants. The problems found in the agricultural sector in Monta Baru Village include dependence on the use of chemical fertilizers and pest attacks on rice plants. For this reason, efforts or solutions are needed to suppress these problems. One effort that can be done is to use liquid organic fertilizers and botanical pesticides on plants. The first step is to provide socialization related to liquid organic fertilizer and botanical pesticides to farmers. Next is the application of liquid organic fertilizer and botanical pesticides to the rice plants. This activity was carried out in the Monta Baru Village by involving farmer groups, Woja sub-district BPP, and the Monta Baru community. Both stages of the activity were carried out smoothly and successfully. Evidenced by the enthusiasm of the farmers in participating in socialization activities and the application of liquid organic fertilizer and botanical pesticides.